Assessing the trophic impact of bleaching: the model pair Berghia stephanieae/Exaiptasia diaphana - Silva, Ruben X. G. (2023)
Bleaching events associated with climate change are increasing worldwide, being a major threat to tropical coral reefs. Nonetheless, the indirect impacts promoted by the bleaching of organisms hosting photosynthetic endosymbionts, such as those impacting trophic interactions, have received considerably less attention by the scientific community. Bleaching significantly affects the nutritional quality of bleached organisms. The consequences promoted by such shifts remain largely overlooked, namely on specialized predators that have evolved to prey upon organisms hosting photosynthetic endosymbionts and benefit nutritionally, either directly or indirectly, from the available pool of photosynthates. In the present study, we advocate the use of the model predator-prey pair featuring the stenophagous nudibranch sea slug Berghia stephanieae that preys upon the photosymbiotic glass anemone Exaiptasia diaphana to study the impacts of bleaching on trophic interactions. These model organisms are already used in other research fields, and one may benefit from knowledge available on their physiology, omics, and culture protocols under controlled laboratory conditions. Moreover, B. stephanieae can thrive on either photosymbiotic or aposymbiotic (bleached) glass anemones, which can be easily maintained over long periods in the laboratory (unlike photosymbiotic corals). As such, one can investigate if and how nutritional shifts induced by bleaching impact highly specialized predators (stenophagous species), as well as if and how such effects cascade over consecutive generations. Overall, by using this model predator-prey pair one can start to truly unravel the trophic effects of bleaching events impacting coral reef communities, as well as their prevalence over time.